A Model-Structure of a Periplasm-facing State of the NhaA Antiporter Suggests the Molecular Underpinnings of pH-induced Conformational Changes - Schushan, Maya (American Society for Biochemistry and Molecular Biology, 2012)
The Escherichia coli NhaA antiporter couples the transport of H(+) and Na(+) (or Li(+)) ions to maintain the proper pH range and Na(+) concentration in cells. A crystal structure of NhaA, solved at pH 4, comprises 12 transmembrane helices (TMs), arranged in two domains, with a large cytoplasm-facing funnel and a smaller periplasm-facing funnel. NhaA undergoes conformational changes, e.g. after pH elevation to alkaline ranges, and we used two computational approaches to explore them. On the basis of pseudo-symmetric features of the crystal structure, we predicted the structural architecture of an alternate, periplasm-facing state. In contrast to the crystal structure, the model presents a closed cytoplasmic funnel, and a periplasmic funnel of greater volume. To examine the transporter functional direction of motion, we conducted elastic network analysis of the crystal structure and detected two main normal modes of motion. Notably, both analyses predicted similar trends of conformational changes, consisting of an overall rotational motion of the two domains around a putative symmetry axis at the funnel centers, perpendicular to the membrane plane. This motion, along with conformational changes within specific helices, resulted in closure at the cytoplasmic end and opening at the periplasmic end. Cross-linking experiments, performed between segments on opposite sides of the cytoplasmic funnel, revealed pH-dependent interactions consistent with the proposed conformational changes. We suggest that the model-structure and predicted motion represent alkaline pH-induced conformational changes, mediated by a cluster of evolutionarily conserved, titratable residues, at the cytoplasmic ends of TMs II, V, and IX.